DISTRIBUTION OF THE THALLOID LIVERWORT GENUS MARCHANTIA (MARCHANTIACEAE) IN NORTH SUMATRA, INDONESIA - Etti Sartina Siregar; Nursahara Pasaribu; Muhammad Zaidun Sofyan (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- The survey method was successful in identifying the species Marchantia and mapping their distribution in North Sumatra- Eight taxa of Marchantia confirmed in North Sumatra, M. emarginata subsp. cuneiloba has the most widely distributed species. - Species distribution linked to environmental factors like elevation, humidity, rainfall, soil types, slope, solar intensity, and types of land coverABSTRACTMarchantia is one of the large genus complex thalloid liverworts (Marchantiophyta). The species of Marchantia has a wide distribution throughout the world, and occupies a variety of substrates. Studies on the presence and distribution of Marchantia species are still limited in North Sumatra. Therefore, the research was carried out to inventory the species of Marchantia and map their distribution in North Sumatra. Survey method was used to inventory the species of Marchantia, covering 9 locations, namely: Aek Nauli Forest, Bukit Barisan National Forest Park, Bukit Lawang, Resort Cinta Raja, Dolok Tinggi Raja Nature Reserve, Sibayak Mountain, Sicike-cike Natural Park, Silima-lima waterfall, and Taman Eden 100 Natural Park. Geographic Information System (GIS) was used to map the distribution of the species. The results showed that there were eight taxa of Marchantia confirmed in North Sumatra, namely, M. acaulis, M. emarginata subsp. emarginata, M. emarginata subsp. cuneiloba, M. geminata, M. paleacea subsp. paleacea, M. polymorpha, M. treubii, and Marchantia sp. The most widely distributed species of Marchantia is M. emarginata subsp. cuneiloba, found in 7 study locations. Species with the least distribution are M. treubii and Marchantia sp., each species found only in one location. Marchantia spp. in North Sumatra spread at an altitude of 77 to 1976 m alt, occupying habitats with 6 types of soil (orthic acrisol, humic andosol, humic acrisol, and humic cambisol), with rainfall of 1800-3600 mm/year. Marchantia species are found on sloping plains to steep, in various habitat, namely secondary forest, primary and secondary forest borders, dryland farming, primary and plantation borders, and plantations. The results of this study are important for the conservation of Marchantia spp. in North Sumatra considering the many benefits of the species.